2004
DOI: 10.1373/clinchem.2004.032292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Specific Gravity and Creatinine for Normalizing Urinary Reproductive Hormone Concentrations

Abstract: Background: Specific gravity (SG) may perform as well as creatinine (CR) correction for adjusting urinary hormone concentrations, as well as offer some advantages. We compared the two methods and applied them to US and Bangladeshi specimens to evaluate their use in different populations. Methods: Pearson correlations between serum concentrations and SG, CR, and uncorrected urinary concentrations were compared using paired daily urine and serum specimens from one menstrual cycle from 30 US women. Corrected urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
211
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 277 publications
(223 citation statements)
references
References 32 publications
(30 reference statements)
8
211
0
1
Order By: Relevance
“…Spot-urine Se results were then adjusted for specific urine gravity (SG) to the overall average gravity of the study population of 1.018 g/ml (Spot-urine Se*(1.018À1)/ (SGÀ1)). This method was preferred to creatinine adjustment, as it is less sensitive to age, gender, body size and nutritional status (Miller et al, 2004;Suwazono et al, 2005). Fifteen individuals (12%) had urine gravity under 1.010 g/ml, which is considered low, but as no individual presented highly diluted urine samples (p1.001 g/ml), no one was excluded (Vahter et al, 2006).…”
Section: Sampling and Analyses Of Biomarkers Of Se Statusmentioning
confidence: 99%
“…Spot-urine Se results were then adjusted for specific urine gravity (SG) to the overall average gravity of the study population of 1.018 g/ml (Spot-urine Se*(1.018À1)/ (SGÀ1)). This method was preferred to creatinine adjustment, as it is less sensitive to age, gender, body size and nutritional status (Miller et al, 2004;Suwazono et al, 2005). Fifteen individuals (12%) had urine gravity under 1.010 g/ml, which is considered low, but as no individual presented highly diluted urine samples (p1.001 g/ml), no one was excluded (Vahter et al, 2006).…”
Section: Sampling and Analyses Of Biomarkers Of Se Statusmentioning
confidence: 99%
“…Urinary hormone values were adjusted by specimen specific gravity (17). Specific gravity measurements were taken with a hand-held urine specific gravity refractometer (Atago Uricon-PN, NSA Precision Cells, Inc).…”
Section: Urine Assaysmentioning
confidence: 99%
“…Several studies have shown that the specific gravity-adjustment method for correcting urine dilution introduced less variability to datasets when compared to the creatinine-adjustment method (Ikeda et al, 2003;Miller et al, 2004;Pearson et al, 2009). The main assumption in specific gravity-adjustment is that changes in urinary flow rate do not affect the relative ratio between the mass of the xenobiotic and the mass of the total dissolved solids (SG) in a urinary spot sample (Pearson et al, 2009).…”
Section: Estimation Of DI Using Urinary Biomarker Concentrationsmentioning
confidence: 99%